Time, work and leisure : Life changes in England since 1700 - Cunningham, Hugh (Book collections on Project MUSE., 2014)
Hugh Cunningham traces the history of the relationship between work and leisure, from the 'leisure preference' of male workers in the 18th century, through the increase in working hours in the later 18th and early 19th centuries, to their progressive decline from 1830 to 1970.